Elaiophylin Inhibits Tumorigenesis of Human Uveal Melanoma by Suppressing Mitophagy and Inducing Oxidative Stress via Modulating SIRT1/FoxO3a Signaling - Zhu, Xue; Zou, Wenjun; Meng, Xinmin; Ji, Jiali; Wang, Xun; Shu, Hong; Chen, Yuan; Pan, Donghui; Wang, Ke; Zhou, Fanfan (Frontiers in Oncology, 2022)
Uveal melanoma (UM) is the most common primary intraocular tumor in adults, which is associated with poor prognosis. Up to 50% of UM patients develop metastasis. Therapeutics that have proven effective in cutaneous melanoma have little success in treating UM, possibly due to its low mutational burden. Therefore, new drug therapies are highly desired for UM. Our in vitro studies showed that Elaiophylin, a late-stage autophagy inhibitor, exhibited an outstanding anticancer activity in human UM cell lines and human UM primary cells through suppressing mitophagy, inducing oxidative stress and leading to autophagic cell death. Our mechanistic study revealed that Elaiophylin exerted its effect by down-regulating SIRT1 and thus influencing deacetylation and mitochondrial localization of FoxO3a. In our confirmatory experiments, SRT1720, a SIRT1 specific activator, could attenuate Elaiophylin-induced inhibition of mitophagy and elevation of oxidative stress, and such effects was partly reversed by FoxO3a knockdown. Our further in vivo studies showed that Elaiophylin dramatically inhibited tumor growth in the human UM xenograft mouse model, which was accompanied with a decreased SIRT1 expression. Thus, the current study is the first to demonstrate that Elaiophylin has a potent anti-cancer effect against UM, which activity is possibly mediated through regulating SIRT1-FoxO3a signaling axis. And Elaiophylin may be a new and promising drug candidate to treat human UM.